2015
DOI: 10.1007/s10903-015-0202-4
|View full text |Cite
|
Sign up to set email alerts
|

Different Patterns in Health Care Use Among Immigrants in Spain

Abstract: This study aims to analyze the differences in the use of primary care (PC), hospital, and emergency services between people born in Spain and immigrants. Data were obtained from the 2006 Spanish National Health Survey. The sample was composed of individuals aged 16-64 years from Spain and the seven countries with most immigrants in Spain (n = 22,224). Hierarchical multiple logistic regression models were fitted. Romanian men were less likely to use health care at all levels compared to men from other countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Distribution of studies regarding publication year was as follows: 8 studies published in 2013 [ 17 , 22 24 , 27 , 28 , 41 , 42 ], 15 in 2014 [ 14 – 16 , 19 , 21 , 30 , 32 , 33 , 35 , 36 , 38 , 40 , 43 , 44 , 47 ], 10 in 2015 [ 13 , 18 , 25 , 26 , 29 , 31 , 34 , 45 , 46 , 48 ] and 3 in 2016 [ 20 , 37 , 39 ]. The majority of the publications analysed data from European countries (28; 78%), both North and Central (12) (Norway [ 13 15 , 19 , 20 ], Denmark [ 45 ], Sweden [ 35 ], the Netherlands [ 17 , 32 , 34 , 40 ] and Austria [ 41 ]) and South Europe (15) (France [ 22 , 36 ], Italy [ 18 , 24 , 29 , 37 , 43 ], Spain [ 23 , 27 , 28 , 31 , 38 , 39 , 46 ] and Portugal [ 33 ]) and 1 from the UK [ 26 ]. Seven papers (19%) explored this issue in North America (2 from USA [ 30 , 34 ] and 5 from Canada [ ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Distribution of studies regarding publication year was as follows: 8 studies published in 2013 [ 17 , 22 24 , 27 , 28 , 41 , 42 ], 15 in 2014 [ 14 – 16 , 19 , 21 , 30 , 32 , 33 , 35 , 36 , 38 , 40 , 43 , 44 , 47 ], 10 in 2015 [ 13 , 18 , 25 , 26 , 29 , 31 , 34 , 45 , 46 , 48 ] and 3 in 2016 [ 20 , 37 , 39 ]. The majority of the publications analysed data from European countries (28; 78%), both North and Central (12) (Norway [ 13 15 , 19 , 20 ], Denmark [ 45 ], Sweden [ 35 ], the Netherlands [ 17 , 32 , 34 , 40 ] and Austria [ 41 ]) and South Europe (15) (France [ 22 , 36 ], Italy [ 18 , 24 , 29 , 37 , 43 ], Spain [ 23 , 27 , 28 , 31 , 38 , 39 , 46 ] and Portugal [ 33 ]) and 1 from the UK [ 26 ]. Seven papers (19%) explored this issue in North America (2 from USA [ 30 , 34 ] and 5 from Canada [ ...…”
Section: Resultsmentioning
confidence: 99%
“…The largest number of papers (18) used information from administrative [ 13 – 16 , 18 20 , 23 , 25 , 29 , 33 , 35 , 37 , 39 , 43 ] or insurance system databases [ 32 , 34 ] and specific hospital registries [ 28 ] as source of information. Among the 16 papers (44.4%) that analysed healthcare surveys, where people report their individual healthcare use, 14 studies used population-based surveys which were elaborated for other purposes [ 17 , 21 , 22 , 24 , 26 , 30 , 36 , 38 , 40 , 44 , 46 48 ] while 3 of the surveys were specifically designed to explore immigrants healthcare use [ 31 , 41 , 42 ]. Only 2 studies [ 33 , 45 ] (5.6%) combined health survey and administrative information and 1 study also used a national survey for general practitioners (GPs) [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of European studies, published in 2010, found “contrasting results” [ 3 ]. Later analyses from Italy, Netherlands, Germany, Denmark, Spain, and United Kingdom have reported both comparatively high and relatively low use of hospital services among migrants [ 4 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature generally indicates a lower use of healthcare services by the immigrant population, at both national (Gimeno‐Feliu et al, ; Villarroel & Artracoz, ) and international level (Berchet, ; Franchi et al, ), and a lower rate of drug prescription and consumption. This might be explained by the “healthy immigrant effect” already mentioned, but another possible factor that cannot be ruled out is greater difficulty in obtaining access to these services (Gimeno‐Feliu et al, ; Vazquez et al, ).…”
Section: Introductionmentioning
confidence: 99%